The epidemiology and clinical feature of selective immunoglobulin a deficiency of Zhejiang Province in China. Issue 10 (26th July 2020) - Zhang, Junwu; Kong, Wanzhong; Ni, Jinyao; Guo, Zhen; Yang, Xunjun; Cao, Qun; Wang, Sheliang; Feng, Yijun; Zhou, Ying; Weng, Wei; Liang, Shanyan; Li, Shuang; et al.
Abstract: Background: Selective immunoglobulin A deficiency (SIgAD) is the most common primary antibody deficiency disease and frequently reported in the Western countries. However, large‐scale epidemiologic studies on SIgAD in China are still lacking. Methods: The clinical information of 555 180 subjects (age >4 years) including the outpatient, inpatient, and healthy subjects who had ordered serum immunoglobulin A, G, M in 9 hospitals of Zhejiang Province in China was collected. The SIgAD individuals were defined as IgA level <0.07 g/L with normal levels of serum IgG and IgM, whose age should be over 4 years, and any other secondary diseases causing SIgAD were also excluded. Then, the geographical and prevalence distribution of SIgAD individuals in Zhejiang Province and patients' clinical characteristics at the time of diagnosis were also reviewed. Result: Among these 555 180 subjects who had ordered the immunoglobulin evaluation, the prevalence of SIgAD was 109/555180 (0.02%). The ratio of male to female of these SIgAD individuals was 1:1.37, which also included 87 adults (≥18 years) and 22 children (18 > age >4 years). For adults, the common clinical features were infections (43/87, 49.43%), autoimmune disorders (31/87, 35.63%), allergic cases (5/87, 5.75%), and tumor cases (4/87, 4.60%). Additionally, infectious diseases (20/22, 90.91%), autoimmune disorders (4/22, 18.18%), and allergic cases (1/22, 4.55%) were found in 22 children. Conclusion: We first describe a large cohort of SIgAD individuals of Zhejiang Province in China. The incidence was 0.020%. The common clinical features were infection, autoimmune disorders, tumor, and allergy, and the infection rate was higher in children than the adults.